Potential of biomethane-based energy production from livestock waste biomass resources in Ethiopia - Tolessa, Amsalu (Frontiers in Energy Research, 2023)
Understanding the potential of biomass sources and their types, quality, and regional distribution is crucial for modern energy production. This study evaluates the biomethane energy potential of livestock waste from six different categories of livestock across all Ethiopian regions using livestock statistics (2020–21), standard procedures, publicly accessible data, and literature. To evaluate the bioenergy potentials, the amount of dry matter per head, collection efficiency, biogas yields of respective livestock waste, and the calorific value of biogas and biomethane were used. The total biomethane and corresponding bioenergy potential of livestock residues in Ethiopia are estimated to be 3,321 hm3 y-1 and 118,906 TJ y-1, respectively. The biomethane combustion in a combined heat and power system is expected to produce roughly 11.4 TWh y-1 of electricity and 13.9 TWh y-1 of thermal energy. The estimated electrical energy could supply 11%, 31%, and 81% of Ethiopia’s total primary energy consumption, production, and total electricity generated in Ethiopia in 2019, respectively. The finding demonstrates that biomethane-based energy production via anaerobic digestion based on livestock waste has the potential to meet a significant portion of Ethiopia’s current energy needs.